Duties of Receiver and Manager - Hj Ab Latif, Samsar Kamar bin (Journal of Malaysian and Comparative Law, 2019)
The legal duties of receivers are derived from the terms of their contract of appointment, the general common law, the statutes, secondary legislation and rules in the profession. The duties of a receiver are owed to the company because a receiver is usually designated as the company’s agent. However, under the terms of his appointment, generally it is clear that he has primary obligation to the debenture holder as well - principally, to obtain the charged assets and realise them with a view to paying the secured creditor’s debt.